Numerical Simulation of Tandem Shaped Charge Penetrating Armored Target under Explosive Loading - Jianping Yin; Conghui Duan; Yangyang Han; Zhijun Wang; Jie Chen (Shock and Vibration)
Tandem shaped charge is one of the hotspots in the research of antiarmor ammunition at present, but because of the shortcoming that the front-stage jet penetrates and detonates ERA (Explosive Reactive Armor), then it will affect the rear-stage jet to penetrate the main armor. Our research team proposes that the front charge of the tandem shaped charge can be designed as a low-density material charge liner so that the front-stage low-density jet can penetrate a small hole in the reactive armor without detonating. The rear-stage main charge forms a main jet through the small hole to penetrate the main armor. In this article, the damage of tandem shaped charge to armored target is studied when copper and new modified PTFE (polytetrafluoroethylene) materials are used as front-stage charge liner, and the numerical simulation results are verified by experiments. The numerical results show that the Cu (copper) jet formed by tandem shaped charge of double-copper material has strong impact performance. The interlayer explosive in reactive armor is detonated in the process of penetrating reaction armor, which weakens the penetration ability of the main rear-jet. However, the interlayer explosive in the reactive armor is not detonated during the penetration of the double-material tandem shaped charge. The front-stage modified PTFE jet and the rear-stage main jet are not affected by the explosion loading before penetrating the main armor. The experimental results show that the double-material tandem shaped charge overcomes the shortcoming of the influence of the front-stage explosion, and the penetration depth of the main armor reaches 703 mm, which is 14.3% higher than the penetration ability of the double-copper tandem shaped charge, which is basically consistent with the numerical simulation results. It provides a reference for improving the damage ability of tandem shaped charge to armored target.